Agronomic bases of precision barley production - Molnárová, Juliana (Acta Agraria Debreceniensis, 2012)
To ascertain the importance of individual preciosion factors in achieving yield and quality of malting barley, we established a multifactor experiment at the research station of the Slovak University of Agriculture in Nitra in 2009 and 2010. Four variants of fertilization, 2 ways of soil cultivation and four varieties ’Bojos’, ’Kangoo’, ’Marthe’ and ’Xanadu’ were observed. From the quality indicators the nitrogen content (%) was observed. The results were statistically analyzed by using a multifactor analysis of variance by using Statistica 8, the program Statgraphics. The difference between years was statistically significant (1.87 t ha-1) in favour of 2010. The difference was also significant between the varieties ’Bojos’ and ’Kangoo’(1.07 t ha-1), respectively. ’Martha’ and ’Xanadu’ as well as ’Kangoo’ (0.56 resp. 0.33 t ha-1). Conventional soil cultivation in comparison with a minimalization technology, demonstrated a tatistically insignificant increase of yield. Significant differences were obtained between the variants of fertilization. Treatment by using Condit (b-var.) showed a very positive impact in climatic favorable year (2010) with a yield result of 7.42 t ha-1. In comparison with an untreated control, the difference in yield was 0.89 t ha-1. A significant increase of yield was achieved by using the combination of solid fertilizer with foliar fertilizer (LAV + Hakofyt, var.c) 0.47 t ha-1. The crude protein content was statistically influenced by a variety and year. In 2009, the crude protein content was above average (12.38%). Significantly lower attributes were achieved in 2010 (9.90%). From the studied/observed varieties the lowest crude protein content was showed by a variety ’Kangoo’ (1.68%).